قیاس مخاطر الاستثمار في الأسواق المالیة وتأثیرها على سلوك المستثمرین - نعجة , عبد الرحمان; مغنیة , هواري; بختي, زولیخة (Finance and Business Economies Review, 2017)
Abstract: This study aims to analyse investment risks nature and sources in Islamic Financial Products and its Ethical counterpart arising from its investing, and also to demonstrate the impact of their performance and risks measuring on the investor's behavior. Secondly, The Performance analysis method is used to compare the two selected benchmarks chosen from among the (DJIM) family of the Canadian Stock Market, utilising daily data of the close prices of the Islamic index (CANI) and its Ethical counterpart (CAN) covering the period from (January 2005 to December 2015). The results show that the Islamic index (CANI) outperform and was more volatility sensible than its Ethical counterpart (CAN), particularly during the period of the Sub-prime Crisis in 2008. Finally, the analysis of the correlation rate shows that there was no significant link between the studied indices and US (T-Bill), which denies the existence of the benchmark price risk. The study affords some of recommendations among them: improving the competitiveness in the Islamic Financial Markets (a), by using Modern Information Systems (b) and the independence of Shariah Boards of Islamic Banks (c), to manage and hedge risks.